Laparoscopic nerve-sparing radical hysterectomy for bulky cervical cancer (≥6 cm) after neoadjuvant chemotherapy: A multicenter prospective cohort study. (October 2016) - Yang, Yongxiu; Qin, Tiansheng; Zhang, Wei; Wu, Qiyan; Yang, Aihong; Xu, Feixue
Abstract: Objective: The study aimed to evaluate the clinical outcomes of laparoscopic nerve-sparing radical hysterectomy (LNRH) for bulky-stage cervical cancer (lesion ≥ 6 cm) after neoadjuvant chemotherapy (NAC). Methods: This study prospective recruited patients with pathology-confirmed cervical cancer presenting as a bulky mass (lesion ≥ 6 cm). Subjects included patients who underwent laparoscopic radical surgery. They were assigned to one of two groups by surgical method: patients who underwent LNRH after NAC and patients who underwent classical laparoscopic radical hysterectomy (LRH) after NAC. We compared the patients' general clinical characteristics, surgical profiles, pathological findings and adjuvant therapies between the two groups. Recovery of bladder and intestinal function was evaluated by questionnaire. Patients were followed for up to 1 year to determine the maintenance of effect. Results: Compared with patients treated with LRH, patients who underwent LNRH presented no significant differences in age, surgery characteristics, pathological findings, adjuvant therapies or main adverse effects. The mean duration of residual urine <50 mL in the LNRH group was 11 days, much shorter than that in the LRH group (18 days; P < 0.001). The period of passage of gas by anus was shorter (38.9 ± 4.1 h) in LNRH patients than that in LRH patients (56.5 ± 4.0 h; P < 0.001). The urinary and intestinal symptoms were evaluated 1 year after surgery. The recovery of urinary and intestinal function of patients was better in the LNRH group than in the LRH group. Conclusion: LNRH is a safe and feasible surgical management for bulky-stage cervical cancer patients (lesion ≥ 6 cm), and after NAC, the urinary and intestinal function of patients in LNRH group showed better recovery compared with functions in the LRH group. The technique is relatively new, and its oncologic efficiency has not yet been fully established. Prospective randomised controlled studies with an increased number of patients and long-term postoperative follow-up should be carried out to investigate the effect of this therapeutic strategy for bulky-stage cervical cancer. Highlights: To evaluate the clinical outcomes of laparoscopic nerve-sparing radical hysterectomy (LNRH) for bulky stage cervical cancer (lesion ≥ 6 cm) after neoadjuvant chemotherapy (NAC). The LNRH after NAC with TC for bulky stage cervical cancer confirmed to the urinary and intestinal function recovered better. The latest study of the patients with bulky stage cervical cancer subjected to this therapeutic strategy.